Hustle harder, hustle smarter - Jackson, Curtis, 1975- (Amistad, an imprint of HarperCollinsPublishers, 2020)
"Curtis '50 Cent' Jackson opens up about his ... comeback--from tragic personal loss to thriving businessman and cable's highest-paid executive--in this unique self-help guide ... In his early twenties [he'd risen] to the heights of fame and power in the cutthroat music business. A decade ago the multi-platinum selling rap artist decided to pivot. His ability to adapt to change was demonstrated when he became the executive producer and star of Power, a ... crime drama centered around a drug kingpin's family ... Now, in his most personal book, [he] shakes up the self-help category with his unique, cutting-edge lessons and hard-earned advice on embracing change"--